EXPLORATION OF STUDENT ACTIVITY IN LESSON STUDY LEARNING WITH TRANSCRIPT BASED LESSON ANALYSIS USING NVIVO - Amroh; Susanti, Nova; Dani, Rahma (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This study aims to describe the learning process that takes place when using lesson study based on Transcript Based Lesson Analysis (TBLA) in the climate change course and describes the exploration of lesson study learning in the climate change course with Transcript based lesson analysis using nvivo. This study uses a qualitative method with a case study approach, where data is collected through videos, voice recordings and documentation that is made into a conversation transcript in excel consisting of numbers, minutes, seconds, speakers and utterances, then the excel is analyzed using NVivo. The results of the analysis show that the TBLA-based lesson study method increases the active involvement of students in group discussions, student-teacher interactions, and in individual learning activities. The use of NVivo allows efficient and systematic data processing, providing visualization of interactions in the form of word clouds, word trees, and graphs to identify key themes in learning. This study is the first to use NVivo to analyze Transcript Based Lesson Analysis (TBLA) data in the context of climate change learning. Previously, TBLA analysis was carried out manually, which was less efficient and potentially biased. The use of NVivo speeds up analysis, increases accuracy, and allows for more complex data visualization.